Obtaining consent from patients - the gap between law and practice /Gurmit Kaur Gopal Singh - Gurmit Kaur, Gopal Sigh (2009)
The doctrine of informed consent being an important communication tool for medical treatment administered towards a patient has been a continuing interest throughout the year.